The Effects of Financial Literacy on the Financial Performance of Micro Businesses in Mezam Division - Takoutio, Feudjio virginie (International Journal of Finance, 2025)
Purpose: Over the years, the greatest desire of most people had been that of achieving high financial performance but the access to that requires the knowledge of financial literacy. This article had as aim to investigate the influence of financial literacy on the financial performance of micro businesses in Mezam. Our objective was achieved by breaking down financial literacy into three variables (debt management literacy, budgeting skills, and book keeping). Methodology: Data collected through questionnaires were analyzed using the Ordinary Least Squares as estimation technique. Findings: After regression, the results of the article revealed that all the three variables considered under financial literacy have positive and significant effect on the financial performance of micro businesses. Unique Contribution to Theory, Policy and Practice: Therefore, to succeed in business and increase their financial performance, owners of micro business should make an effort to be train on how to manage their debt effectively, how to keep records and how to plan a budget.